Situation Report: Poland, 28 July 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to President Nixon's Intended Trip to china National Holiday: Youth Meeting in Katowice Gierek, Cyrankiewicz Meeting Soviet Leaders Jaroszewicz in Berlin: Economic Relations with the GDR Syrian Foreign Minister Visits Poland Economic Performance in the First Half of 1971 National Economic Conference on Efficient Management of Supplies Reductions of Prices and Customs Duties Citizens' Platform: Barcikowski Answers Questions on Agriculture